Studi Deskriptif Prinsip-Prinsip Pelayanan Menurut Efesus 4:11-16 - Victor Immanuel Rahardjo; Roberth Ruland Marini (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2020)
There are many problems in ministry because God's servants do not have principles or standards of service that become a reference so that it has an impact on conflicts of interest so that God's church does not experience growth. Calling and equipping ministers to build up the body of Christ which must be built up to the certain standards and qualities desired by God. By using descriptive qualitative analysis in Ephesians 4: 11-16, it can be explained how the minister is called, equipped to produce unity of faith in the Son of God, produce full maturity and produce a growth rate according to the fullness of Christ. Every believer is required to experience progress and growth in his life both physically and spiritually. This growth has a definite and clear direction that is sourced and focused on Christ Himself. The expected result from understanding the principles of service according to Ephesians 4: 11-16 is the growth of service, both in quantity and quality. That is having the confidence of salvation, a healthy prayer life, perseverance in reading the Word of God, faithfulness in fellowship and the habit of witnessing.